2013
DOI: 10.2989/16085906.2013.871568
|View full text |Cite
|
Sign up to set email alerts
|

Just jokes! Icebreakers, innuendo, teasing and talking: The role of humour in HIV/AIDS peer education among university students

Abstract: Peer conversation provides an important platform for people to explore and disseminate sexual health knowledge. Humour forms part of conversations held between peers including those where sexual health and sexual decisions are discussed. The central argument of this article links conversation, humour and peer education. Drawing on interviews and diaries kept by 12 student peer educators over a two-month period in a South African university, the article explores the forms and functions of humour in instigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Following our secondary search for studies that described the interventions identified, we found 27 additional manuscripts. Thus, the total number of manuscripts reviewed was 112 [19‐130]. These manuscripts described 74 unique intervention research studies (Table 1) […”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following our secondary search for studies that described the interventions identified, we found 27 additional manuscripts. Thus, the total number of manuscripts reviewed was 112 [19‐130]. These manuscripts described 74 unique intervention research studies (Table 1) […”
Section: Resultsmentioning
confidence: 99%
“…About three quarters of studies (56, 76%) had no youth engagement at the pre‐intervention phase [19,22,29,30,32,34,37‐42,44,46‐48,50‐53,55‐58,61‐66,68‐70,73‐86,88‐90,129,130].…”
Section: Resultsmentioning
confidence: 99%
“…As such, the practices of night-time excess may extend into 'inappropriate' joking becoming an end in its own right. Cooper and Dickinson (2013) identify that such joking can create tense environments that close down discussion completely, again raising concerns as to the extent to which rape prevention campaigns in bars and clubs will be attended to, taken seriously if noticed and their messages internalised.…”
Section: Having Fun When Out In the Eveningmentioning
confidence: 99%
“…So you'd probably just start like sort of taking the mickey out of the content of it [the campaign] (FG6). ' Cooper and Dickinson (2013) identify that humour can act as a 'gateway' to discussing taboo and private subjects with Kramer (2011) also arguing that the framing of a joke can transform a disturbing act into a humorous one without necessarily detracting from the disturbing nature of the act itself. However, there is legitimacy in suggesting that such 'taking the mickey' will be enhanced within the youth focused night-time environment.…”
Section: Having Fun When Out In the Eveningmentioning
confidence: 99%
“…Research also identifies how facilitators struggle to operationalize concepts and ideas—often introduced to them in English—into local language and concepts [ 19 , 20 ]. This highlights the on-going issue of the ‘importing’ of interventions into local contexts [ 13 ].…”
Section: Introductionmentioning
confidence: 99%